2009
DOI: 10.1161/circheartfailure.108.794065
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Stretch-Induced Force Response in Failing Human Myocardium Caused by Impaired Na + -Contraction Coupling

Abstract: Background-Stretch elicits an immediate, followed by a delayed, inotropic response in various animal models and failing human myocardium. This study aimed to characterize functional differences in the stretch response between failing and nonfailing human myocardium. Methods and Results-Experiments were performed in muscle tissue from 86 failing and 16 nonfailing human hearts.Muscles were stretched from 88% to 98% of optimal length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 55 publications
3
13
1
Order By: Relevance
“…On the contrary, Reuter et al have reported no difference in the rate of relaxation or the contractile function of right atrial cardiac muscles from type 2 diabetic patients undergoing CABG [26]. However, the contractile and relaxation measurements reported in that study were much lower in magnitude when compared to values reported in other studies using human right atrial cardiac muscles [27,28] and our study (Table  2). This may be related to tissue degradation in their samples due to prolonged loading with a fluorescence indicator, while our experimental measurements were obtained within 90 minutes after dissection.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…On the contrary, Reuter et al have reported no difference in the rate of relaxation or the contractile function of right atrial cardiac muscles from type 2 diabetic patients undergoing CABG [26]. However, the contractile and relaxation measurements reported in that study were much lower in magnitude when compared to values reported in other studies using human right atrial cardiac muscles [27,28] and our study (Table  2). This may be related to tissue degradation in their samples due to prolonged loading with a fluorescence indicator, while our experimental measurements were obtained within 90 minutes after dissection.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies reported that the Frank-Starling mechanism is maintained in patients with reduced EF [28,30]. More recently, patients with preserved EF showed a preserved static (intrinsic to the heart) Frank-Starling mechanism [31], whereas the beat-to-beat dynamic (including the heart-arterial interaction) Frank-Starling mechanism was impaired in these patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…13, 47 Angiotensin II, endothelin and slow stretch activation are known activators of NHE-1. 47,48 Na + -influx through NHE-1 has been suggested to promote concentric LVH through Ca 2+ -dependent mechanisms. 49, 50 In a small patient study, amiloride was reported to improve exercise hemodynamics and LVEDP in heart failure patients.…”
Section: Discussionmentioning
confidence: 99%
“…After LPS 8 hours, LV muscle strips from seven hearts of NT (n = 23) and five hearts of MH (n = 17) were isolated and equilibrated in Tyrode's solution with 2.5 mM calcium at 38.0°C as described before (24). One heart of MH was missed due to malfunction of the technical setup.…”
Section: Isolated Cardiac Muscle Stripsmentioning
confidence: 99%